Corporate governance and risk-based auditing: The Malaysian evidences - zainal abidin, nor hafizah; haron, hasnah`; shahbudin, amirul shah (2011)
Business globalization, advancement in technology and demands for value added services has recognized the importance of risk based internal auditing approach. This paper examines from agency perspective how internal audit experience, audit committee attributes, risk management and internal control systems influence the implementation of risk based auditing. The study analysed data collected from 117 heads of internal audit function in public listed companies in Bursa Malaysia as at October 2010. Findings indicate that audit committee concerns and risk management system are found to be significantly and positively related to the implementation of risk based auditing. However, internal audit experience, audit committee qualification, and internal control system were found not to be significant predictors of the implementation of risk based auditing. This study provides empirical evidence to support the findings as suggested by previous qualitative studies. In addition, this paper enhanced the scope of implementation of risk based auditing procedures beyond the audit planning stage.